Hardware and software of the “smart” boat oar for the applied force measurement system - Parakhin, Ruslan; Levytska, Tetiana; Piatykop, Olena; Balalaieva, Olena (Національний університет “Львівська політехніка”, 2025)
Assessment of the volume and quality of a rower's efforts during training plays an important role in preparing for competitions and improving his results. The article reviews existing commercial solutions, such as rowing simulators and individual sensor devices. It was determined that such proposals allow recording the frequency or trajectory of movement, but do not measure force. They also have limited functionality in real water conditions or high cost. Therefore, it is proposed to bring rowers' training into the realm of modern technologies for measuring and analyzing information in real time. For this purpose, a device mounted on an oar for numerically assessing individual aspects of rowing technique and corresponding software are proposed. Approaches to creating an embedded system for measuring force, orientation, and vibration response of an oar are investigated. The hardware part of the device is developed based on the Seeed XIAO nRF52840 board with low power consumption, built-in Bluetooth, accelerometer, and gyroscope. A strain gauge in combination with an analog-todigital converter HX711 was used as a force sensor. The disadvantages of previous solutions based on Arduino Nano and the HC-05 module are described, in particular, high power consumption, unstable communication, and non-compliance with modern requirements. The choice of a real-time operating system is described. The capabilities of Zephyr OS, FreeRTOS, and Mbed OS are compared. FreeRTOS is preferred as a system with a minimalist kernel sufficient for flow control and stable operation of sensors in real time. The device's power consumption in different modes is analyzed. The use of sleep modes for the microcontroller, sensors, and other components is proposed. A battery discharge curve is constructed that takes into account the nonlinear relationship between voltage and residual charge, which allows for accurate determination of the charge level in field conditions without external indicators. The article also describes the principle of device calibration. A multi-point force calibration method with interpolation between key points is presented. Оцінка обсягу та якості зусиль весляра у процесі тренування відіграє важливу роль у підготовці до змагань та покращенні його результатів. У статті розглянуто існуючі комерційні рішення, такі як гребні тренажери та окремі сенсорні пристрої. Визначено, що такі пропозиції дозволяють фіксувати частоту або траєкторію руху, але не вимірюють силу. Також вони мають обмеженість функціональності в реальних умовах на воді або високу вартість. Тому пропонується вивести тренування веслярів у площину сучасних технологій вимірювання та аналізу інформації у реальному часі. Для цього пропонується пристрій, що встановлюється на весло для чисельної оцінки окремих аспектів техніки веслування та відповідне програмне забезпечення. Досліджено підходи до створення вбудованої системи вимірювання сили, орієнтації та вібраційного відгуку весла. Розроблено апаратну частину пристрою на основі плати Seeed XIAO nRF52840 з низьким енергоспоживанням, вбудованим Bluetooth, акселерометром і гіроскопом. У якості датчика сили використано тензодатчик у поєднанні з аналого-цифровим перетворювачем HX711. Описано недоліки попередніх рішень на основі Arduino Nano та модуля HC-05, зокрема високе енергоспоживання, нестабільність зв’язку та невідповідність сучасним вимогам. Описано вибір операційної системи реального часу. Порівняно можливості Zephyr OS, FreeRTOS та Mbed OS. Перевагу надано FreeRTOS як системі з мінімалістичним ядром, достатнім для управління потоками та стабільної роботи сенсорів у реальному часі. Проведено аналіз енергоспоживання пристрою в різних режимах. Запропоновано використання режимів сну для мікроконтролера, сенсорів та інших компонентів. Побудовано криву розрядки батареї, яка враховує нелінійний зв’язок між напругою та залишковим зарядом, що дозволяє точно визначати рівень заряду в польових умовах без зовнішніх індикаторів. Також у статті описано принцип калібрування пристрою. Наведено методику багатоточкового калібрування зусиль з інтерполяцією між ключовими точками.
Апаратне т а програмне забезпечення“розумного” весла для системи вимірювання прикладеної сили
Keywords: Embedded, IoT, Bluetooth®, Realtime OS, microcontroller board, training evaluation, force measurement, вбудовані системи, Інтернет речей, Bluetooth®, операційна система реального часу, мікроконтролерна плата, оцінка тренувань, вимірювання сили; 004.8:519.8